A sea urchin-like structure MgO-MgSiN2 composite powder and a preparation method thereof
By using pseudomorphic magnesite mother salt particles as a reactor and structural template, and employing polysilazane precursors and plasma-enhanced chemical vapor deposition technology, in-situ generation of MgSiN2 and surface whisker growth in the magnesium oxide framework were achieved. This solved the densification problem caused by the pseudomorphic structure of the mother salt and improved the density and purity of the material.
Patent Information
- Application Number
- CN202611402594.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-09-10
AI Technical Summary
In the prior art, the pseudostructure of the mother salt of MgO, a thermal decomposition product of magnesite, leads to low bulk density of the green body. Magnesium oxide requires high temperature and long-term heat preservation during sintering, and it is difficult to achieve densification. The reinforcing phase is unevenly distributed inside the particles, and the interfacial bonding is weak.
Using pseudomorphic particles of mother salt produced by the decomposition of magnesite as a three-dimensional nanoreactor and structure-guided template, the uniform mixing of Mg and Si is achieved through molecular design of magnesium-containing polysilazane precursors. Plasma-enhanced chemical vapor deposition technology is used to generate MgSiN2 in situ inside the magnesium oxide framework and grow whiskers on the surface to form a sea urchin-like structure.
This method achieves spatially ordered and continuous distribution of MgSiN2, avoids the energy consumption of high-temperature sintering, enhances the density and interfacial bonding strength of the material, and improves the purity and conversion rate of the product.
Smart Images

Figure CN122878116B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-value utilization of low-grade mineral resources, specifically to a MgO-MgSiN2 composite powder with a sea urchin-like structure and its preparation method. Background Technology
[0002] During the thermal decomposition of magnesite (MgCO3), the decomposition product MgO retains the crystal morphology and outline of the original magnesite particles, forming a metastable structure with high specific surface area and nanoscale pores, known as the "mother salt pseudomorph." The porous structure inside the pseudomorph particles leads to a decrease in the bulk density of the green body, and the sintering of magnesia requires high temperature and long-term holding to promote densification, consuming a large amount of energy.
[0003] In existing technologies, Chen Qianlin et al. (Chen Qianlin, Yan Wen, Wang Xiao. Synthesis Mechanism of Porous Magnesium-Based Magnesium-Iron-Aluminum Composite Spinel Refractory Aggregate. Journal of the Chinese Ceramic Society, 2023) employed an in-situ decomposition synthesis method, using magnesite and aluminum hydroxide as raw materials, and utilizing the pseudomorphic particles of both as templates to generate magnesium-iron-aluminum composite spinel in situ inside and on the surface of the pseudomorphic particles. The above studies only used the pseudomorphic mother salt as a physical pore-forming template, synthesizing the spinel phase through solid-phase reactions between oxides. However, during the reaction, the high-temperature mass transfer of reactants inside the particles was limited by the solid-phase diffusion coefficient, resulting in limited conversion efficiency of the target spinel phase and a large amount of unreacted intermediate phase remaining in the product.
[0004] Polymer precursor conversion methods can prepare high-purity ceramic materials at relatively low temperatures. For example, Li Tianhao et al. (Li Tianhao, Zhang Jianning, He Liu, Song Yujie. Precursor method for preparing silicon nitride ceramic powder containing sintering aid and its sintering. Journal of the Chinese Ceramic Society, 2024) grafted yttrium and magnesium into a trimethylsilyl-substituted polysilazane precursor. During the pyrolysis of the precursor, metal nitride sintering aids were generated in situ. The silicon nitride ceramic containing the sintering aids could be directly sintered at low temperatures to prepare high-purity porous silicon nitride ceramic blocks with good hardness and thermal conductivity. However, in this study, the metal nitride sintering aids remained solid at high temperatures and could not form an effective liquid phase with silicon nitride to promote particle rearrangement and interstitial densification. A large number of irregular pores existed inside the material, making it difficult to achieve complete densification sintering.
[0005] Patent CN2024105558520 describes a method using silicon powder and magnesium powder as raw materials, cobalt nitrate hexahydrate as a catalyst, and sodium dodecylbenzenesulfonate as a surfactant. Cobalt is loaded onto the surface of silicon powder via liquid-phase reduction. The mixture is then heated sequentially to 1000–1100 °C and held at 1100–1300 °C in a nitrogen atmosphere, followed by furnace cooling and crushing / sieving to obtain high-specific-surface-area cobalt-loaded catalytic nano-sized silicon-magnesium nitride whiskers. This method utilizes liquid-phase reduction to load cobalt onto the silicon powder surface and leverages the catalytic effect of cobalt to promote the nitriding reaction. However, the surfactants and binders introduced during liquid-phase reduction increase the source of impurities, making it difficult to guarantee the uniformity and stability of the cobalt-loaded layer at high temperatures.
[0006] Another patent, CN2022109766383, uses high-silicon magnesite powder and nano-carbon black as the main raw materials, silicon nitride and magnesium powder as additives, and ferric nitrate nonahydrate or nickel nitrate hexahydrate as catalysts. After ball milling and mixing, the mixture is pressed into sheets and then subjected to segmented heating at 1250-1500 ℃ under a nitrogen atmosphere. After crushing and sieving, magnesium oxide-silicon nitride magnesium powder based on high-silicon magnesite is obtained. Although in-situ synthesis at relatively low temperatures is achieved using a carbothermal reduction method, from a structural perspective, during the decomposition of high-silicon magnesite, MgO preferentially crystallizes and forms a dense coating layer on the particle surface, hindering the nitridation reaction of internal SiO2 and the inward diffusion of nitrogen atmosphere and additives. The silicon nitride magnesium phase is only formed near the surface and cannot penetrate deep into the particle interior, resulting in weak interfacial bonding.
[0007] Therefore, this invention proposes a new structural design method to overcome the defects of the "mother salt illusion" of magnesium oxide particles. By using it as a three-dimensional nanoreactor and structural guiding template, the high reactivity and continuous pore channels inherent in the "mother salt illusion" are utilized to guide the gas phase infiltration and reaction, so that the reinforcing phase does not nucleate randomly, but grows along the pre-set template spatial confinement, providing a new path to achieve the spatially ordered distribution and continuity of the reinforcing phase. Summary of the Invention
[0008] To address the shortcomings of existing technologies, this invention provides a MgO-MgSiN2 composite powder with high conversion rate, high purity, dense structure, and a sea urchin-like structure, as well as its preparation method. This invention uses pseudomorphic particles of mother salt produced from the decomposition of magnesite as a three-dimensional nanoreactor and structural guiding template. Through molecular design of a magnesium-containing polysilazane precursor, Mg and Si are uniformly mixed at the molecular scale, allowing the precursor to infiltrate into the nanopores within the magnesia framework. Then, through segmented heat treatment and plasma-enhanced chemical vapor deposition, spatially selective morphology control is achieved, enabling the reinforcing phase (MgSiN2) to precipitate internally as particles and grow on the surface as whiskers. This provides a novel pathway for achieving the spatially ordered and continuous distribution of the reinforcing phase.
[0009] To achieve the above objectives, the specific technical solution of the present invention is as follows:
[0010] This invention provides a method for preparing MgO-MgSiN2 composite powder with a sea urchin-like structure, comprising the following steps:
[0011] In an inert gas atmosphere, an organic solvent solution of organopolysilazane and alkyl magnesium is mixed with a hydrocarbon inert organic solvent and stirred for 2-6 h. The solvent is then removed to obtain a magnesium-containing polysilazane precursor.
[0012] The magnesium-containing polysilazane precursor is dissolved in a hydrocarbon inert organic solvent, a soluble cobalt salt is added, and the mixture is stirred until completely dissolved to obtain an impregnation solution; wherein the mass ratio of the organopolysilazane, the organic solvent solution of alkyl magnesium, and the soluble cobalt salt is 3.0:(1.0~6.0):(0.1~5.0), and the organic solvent solution of alkyl magnesium is based on the mass of magnesium element;
[0013] Magnesium oxide powder with pseudomorphic characteristics of mother salt was placed in an impregnation container, impregnation liquid was added, and after vacuum impregnation, it was subjected to heat curing treatment; the above vacuum impregnation and heat curing steps were repeated 1 to 5 times to obtain the composite precursor;
[0014] The composite precursor was placed in a plasma-enhanced chemical vapor deposition system and heated to 1000-1200 °C at a rate of 5-9 °C / min under a flowing high-purity nitrogen atmosphere, and held for 1-3 h; then heated to 1300-1420 °C at a rate of 2-6 °C / min and held for 3-5 h to obtain a sea urchin-like MgO-MgSiN2 composite powder. The segmented heating rates of the two stages in this invention are optimized based on the pyrolysis kinetics of the precursor and the thermodynamics of whisker growth. In the first heating stage, if the rate is below 5 °C / min, gaseous active species escape due to prolonged gas flow purging, resulting in insufficient nucleation density; if it is above 9 °C / min, it triggers violent pyrolysis and concentrated gas escape, inducing internal stress cracks and disrupting the preferred orientation of the whiskers. In the second stage, if the temperature rise is below 2 ℃ / min, the gaseous precursor will be excessively consumed in the high-temperature range due to long-term purging, resulting in insufficient supersaturation of whisker growth and a decrease in yield; if it is above 6 ℃ / min, the thermal hysteresis effect of the system will cause a significant radial temperature gradient, resulting in asynchronous pyrolysis and crystallization reactions of the inner and outer layers, ultimately leading to product structure stratification and uneven morphology.
[0015] Optionally, the organopolysilazane is IOTA9118 solvent-free liquid polysilazane with a solid content ≥99wt%.
[0016] Optionally, the alkyl magnesium is selected from one or more of dimethyl magnesium, diethyl magnesium, and di-n-butyl magnesium; the solvent of the organic solvent solution of the alkyl magnesium is preferably n-hexane or n-heptane, with a concentration range of 1~2 mol / L.
[0017] Optionally, the hydrocarbon inert organic solvent is selected from one or more of n-hexane, toluene, and xylene.
[0018] Alternatively, the solvent can be removed by vacuum distillation.
[0019] Optionally, the soluble cobalt salt is selected from one or more of cobalt nitrate hexahydrate, cobalt chloride, cobalt acetate, and cobalt sulfate.
[0020] Optionally, the magnesium oxide powder with the pseudomorphic characteristics of mother salt is obtained by calcining high-silica magnesite powder at 400~600 ℃ for 1~3 h, followed by furnace cooling, crushing, and sieving.
[0021] Optionally, the high-silica magnesite powder has a MgCO3 content ≥85wt%, a SiO2 content ≥8wt%, and a particle size ≤0.074mm.
[0022] Optionally, the mass ratio of the magnesium oxide powder with the pseudo-mother salt characteristics to the impregnation liquid is 10:(30~150).
[0023] Optionally, the vacuum impregnation operation is as follows: placing an impregnation container containing magnesium oxide powder with the pseudomorphic characteristics of mother salt and an impregnation solution in a vacuum dryer, evacuating to -0.1 MPa, and maintaining for 20~40 min; when repeating the vacuum impregnation step, placing the cured sample in an impregnation container, adding impregnation solution according to the mass ratio of sample to impregnation solution of 10:(30~150), and then placing it in a vacuum dryer, evacuating to -0.1 MPa, and maintaining for 20~40 min.
[0024] Optionally, the plasma source of the plasma-enhanced chemical vapor deposition system is a radio frequency plasma source with a radio frequency of 10~50 MHz and a radio frequency power of 500~900 W.
[0025] Specifically, the preparation method of the sea urchin-like MgO-MgSiN2 composite powder is as follows:
[0026] Step 1: Place the high-silicon magnesite powder in a tubular atmosphere furnace and calcine it at 400~600 ℃ for 1~3 h. Cool it in the furnace, crush it, and sieve it to obtain magnesium oxide powder with uniform particle size, good dispersibility, and pseudomorphic characteristics of mother salt.
[0027] Step 2: Under an inert gas atmosphere, 3.0 parts by mass of organopolysilazane, 1.0-6.0 parts by mass of alkyl magnesium in an organic solvent solution (based on the mass of magnesium element) and 15.0-55.0 parts by mass of hydrocarbon inert organic solvent are placed in a mechanically stirred reactor and stirred at a speed of 400-600 r / min for 2-6 h. The solvent is removed by vacuum distillation to obtain the magnesium-containing polysilazane precursor.
[0028] Step 3: Dissolve all the magnesium-containing polysilazane precursors obtained in Step 2 in 15-75 parts by mass of hydrocarbon inert organic solvent, add 0.1-5.0 parts by mass of soluble cobalt salt, and stir at 200-400 r / min until completely dissolved to obtain impregnation solution.
[0029] Step 4: Place 10 parts by weight of magnesium oxide powder with the pseudomorphic characteristics of mother salt in an impregnation container, add 30-150 parts by weight of impregnation liquid, place in a vacuum dryer, evacuate to -0.1 MPa, maintain for 20-40 min, remove; then cure at 80-120 ℃ for 3-7 h; repeat the above vacuum impregnation and heating curing steps 1-5 times to obtain the composite precursor; the specific operation of repeating the above vacuum impregnation and heating curing steps is as follows: place 10 parts by weight of the cured sample in an impregnation container, add 30-150 parts by weight of impregnation liquid, place in a vacuum dryer, evacuate to -0.1 MPa, maintain for 20-40 min, remove; then cure at 80-120 ℃ for 3-7 h;
[0030] Step 5: Place the composite precursor in a plasma-enhanced chemical vapor deposition system and heat it to 1000-1200 ℃ at a rate of 5-9 ℃ / min under a flowing high-purity nitrogen atmosphere, and hold it for 1-3 h; then heat it to 1300-1420 ℃ at a rate of 2-6 ℃ / min, hold it for 3-5 h, cool it with the furnace, and ultrasonically disperse it to obtain a sea urchin-like MgO-MgSiN2 composite powder.
[0031] The present invention also provides a sea urchin-like MgO-MgSiN2 composite powder prepared by the above preparation method. The sea urchin-like MgO-MgSiN2 composite powder has a core of pseudo-magnesium oxide particles of mother salt, with MgSiN2 particles dispersed inside and MgSiN2 whiskers radially grown on the surface.
[0032] Compared with the prior art, the advantages of the present invention are:
[0033] This invention utilizes atomic-level homogeneous mixing of polymer precursors to chemically graft Mg atoms onto polysilazane molecular chains. This grafting process involves the active NH bonds on the polysilazane molecular chains undergoing a dealkylation reaction with diethylmagnesium to form chemical bonds, anchoring Mg atoms in a coordinated manner within the molecular backbone. This confines the nucleation sites of MgSiN2 during pyrolysis to the molecular chain segment scale, achieving homogeneous mixing of Mg and Si at the molecular scale and resulting in a more uniform distribution of MgSiN2 in the pyrolysis products. Semi-quantitative XRD analysis reveals that the intensity ratio of MgSiN2 to MgO diffraction peaks initially increases and then decreases under different magnesium excess levels. When the magnesium excess is moderate, the MgSiN2 / MgO peak intensity ratio reaches its maximum, indicating the existence of an optimal magnesium excess range within which the amount of MgSiN2 generated is relatively high and the product phase purity is superior. The method of this invention can achieve in-situ generation of MgSiN2 in the MgO mother salt pseudo matrix, and the yield of MgSiN2 can be optimized by adjusting the magnesium-silicon ratio. At the same time, it avoids incomplete reaction and impurity phase generation caused by uneven distribution of raw materials during mechanical mixing.
[0034] This invention completes the entire reaction in powder form, eliminating the need for a sintering densification stage. This fundamentally avoids the shortcomings of solid-phase sintering aids, which cannot promote particle rearrangement and interstitial densification. The original nanopores inside the pseudomorphic mother salt are not eliminated by sintering, but are filled by MgSiN2 nanoparticles generated in situ by the pyrolysis of the precursor, transforming the pores from structural defects into a space for the composite reinforcing phase. Furthermore, the MgSiN2 whiskers that are radially grown on the surface form a continuous coating layer, resulting in a more compact overall structure of the urchin-like composite powder obtained by this invention.
[0035] This invention introduces cobalt into the precursor molecular layer to achieve uniform distribution of the catalyst at the molecular scale, avoiding the problems of agglomeration and deactivation of the added catalyst at high temperatures, ensuring the uniformity and stability of the cobalt supported layer at high temperatures, and further improving the amount of MgSiN2 whiskers generated on the powder surface.
[0036] The MgO-MgSiN2 composite powder prepared by this invention possesses a unique sea urchin-like structure. By overcoming the defects of the mother salt pseudomorphism, it uses magnesium oxide particles as the core, whose internal pores provide a nanoscale confined space for precursor pyrolysis. MgSiN2 nanoparticles are generated in situ within these internal pores, strengthening the matrix through a pinning effect. The formation of MgSiN2 is not limited by surface densification, and the internal pores are fully utilized, resulting in a more complete reaction. MgSiN2 whiskers on the framework surface grow radially along the lattice-matching direction, and a strong interface is formed between the whiskers and the MgO core through in-situ chemical bonding, avoiding the interface debonding problem encountered during mechanical mixing.
[0037] In summary, the MgO-MgSiN2 composite powder with a sea urchin-like structure prepared by this invention has advantages such as high conversion rate, high product purity, and dense structure. This allows it to be used in magnesia-based unshaped refractories (such as magnesia castables). By utilizing the physical barrier effect of its core-shell coating structure, it inhibits the contact between the internal MgO components and water vapor, thereby delaying the hydration reaction process and reducing the risk of volume expansion and structural cracking of unshaped refractories during curing and heating drying stages. Alternatively, it can be used as a modifying additive for anti-oxidation and anti-slag erosion in carbon-containing refractories (such as magnesia-carbon bricks and magnesia-carbon unfired bricks) to improve the structural stability of products under high-temperature service environments. Attached Figure Description
[0038] Figure 1 The image shows the XRD pattern of the urchin-like MgO-MgSiN2 composite powder prepared in Example 3 of this invention.
[0039] Figure 2 This is a SEM image of the urchin-like MgO-MgSiN2 composite powder prepared in Example 3 of the present invention. Detailed Implementation
[0040] To enable those skilled in the art to clearly and completely understand the technical solution of the present invention, the present invention will be further described in detail below with reference to embodiments. Obviously, the embodiments described herein are only for explaining the present invention and are not intended to limit the scope of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0041] Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the raw materials, methods and equipment used in this invention are conventional raw materials, methods and equipment in the art.
[0042] This invention provides a method for preparing MgO-MgSiN2 composite powder with a sea urchin-like structure, comprising the following steps:
[0043] In an inert gas atmosphere, an organic solvent solution of organopolysilazane and alkyl magnesium is mixed with a hydrocarbon inert organic solvent and stirred for 2-6 h. The solvent is then removed to obtain a magnesium-containing polysilazane precursor.
[0044] The magnesium-containing polysilazane precursor is dissolved in a hydrocarbon inert organic solvent, a soluble cobalt salt is added, and the mixture is stirred until completely dissolved to obtain an impregnation solution; wherein the mass ratio of the organopolysilazane, the organic solvent solution of alkyl magnesium, and the soluble cobalt salt is 3.0:(1.0~6.0):(0.1~5.0), and the organic solvent solution of alkyl magnesium is based on the mass of magnesium element;
[0045] Magnesium oxide powder with pseudomorphic characteristics of mother salt was placed in an impregnation container, impregnation liquid was added, and after vacuum impregnation, it was subjected to heat curing treatment; the above vacuum impregnation and heat curing steps were repeated 1 to 5 times to obtain the composite precursor;
[0046] The composite precursor was placed in a plasma-enhanced chemical vapor deposition system and heated to 1000-1200 °C at a rate of 5-9 °C / min under a flowing high-purity nitrogen atmosphere, and held for 1-3 h; then heated to 1300-1420 °C at a rate of 2-6 °C / min and held for 3-5 h to obtain a sea urchin-like MgO-MgSiN2 composite powder.
[0047] In some embodiments, the alkyl magnesium is selected from one or more of dimethyl magnesium, diethyl magnesium, and di-n-butyl magnesium; the solvent of the organic solvent solution of the alkyl magnesium is preferably n-hexane or n-heptane, with a concentration range of 1~2 mol / L.
[0048] In some embodiments, the hydrocarbon inert organic solvent is selected from one or more of n-hexane, toluene, and xylene.
[0049] In some implementations, the solvent is removed by vacuum distillation.
[0050] In some embodiments, the soluble cobalt salt is selected from one or more of cobalt nitrate hexahydrate, cobalt chloride, cobalt acetate, and cobalt sulfate.
[0051] In some embodiments, the magnesium oxide powder with the pseudomorphic characteristics of mother salt is obtained by calcining high-silica magnesite powder at 400~600 ℃ for 1~3 h, followed by furnace cooling, crushing, and sieving.
[0052] In some embodiments, the mass ratio of the magnesium oxide powder with the pseudomorphic characteristics of mother salt to the impregnation liquid is 10:(30~150).
[0053] In some embodiments, the vacuum impregnation operation is as follows: placing an impregnation container containing magnesium oxide powder with the pseudomorphic characteristics of mother salt and an impregnation solution in a vacuum dryer, evacuating to -0.1 MPa, and maintaining for 20~40 min; when repeating the vacuum impregnation step, placing the cured sample in an impregnation container, adding impregnation solution according to the mass ratio of sample to impregnation solution of 10:(30~150), and then placing it in a vacuum dryer, evacuating to -0.1 MPa, and maintaining for 20~40 min.
[0054] In some embodiments, the plasma source of the plasma-enhanced chemical vapor deposition system is a radio frequency plasma source with a radio frequency of 10~50 MHz and a radio frequency power of 500~900 W.
[0055] In the following specific embodiments, the high-silica magnesite powder contains MgCO3 content ≥85wt%, SiO2 content ≥8wt%, and particle size ≤0.074 mm; the organopolysilazane is IOTA9118 solvent-free liquid polysilazane with a solid content ≥99wt%; in the diethylmagnesium n-hexane solution, the diethylmagnesium solute purity is ≥98%, and the molar concentration of diethylmagnesium is 1.0 mol / L; the anhydrous toluene has a water content ≤50 ppm and a purity ≥99.8%; and the cobalt nitrate hexahydrate has a purity ≥98%.
[0056] Example 1
[0057] The preparation steps of a MgO-MgSiN2 composite powder with a sea urchin-like structure are as follows:
[0058] Step 1: Place the high-silicon magnesite powder in a tubular atmosphere furnace and calcine it at 400 ℃ for 1 h. Cool it in the furnace, crush it, and sieve it to obtain magnesium oxide powder with uniform particle size, good dispersibility, and pseudomorphic characteristics of mother salt.
[0059] Step 2: Under the protection of argon atmosphere, 3.0 parts by mass of organopolysilazane, 1.0 parts by mass of diethylmagnesium in n-hexane solution, and 55 parts by mass of anhydrous toluene are mixed and stirred at 400 r / min for 2 h. The solvent is removed by vacuum distillation to obtain magnesium-containing polysilazane precursor.
[0060] Step 3: Dissolve all the magnesium-containing polysilazane precursor obtained in Step 2 in 15 parts by mass of anhydrous toluene, add 0.10 parts by mass of cobalt nitrate hexahydrate, and stir at 200 r / min until completely dissolved to obtain the impregnation solution.
[0061] Step 4: Place 10 parts by weight of magnesium oxide powder with the pseudomorphic characteristics of mother salt in an impregnation container, add 30 parts by weight of impregnation liquid, and vacuum in a vacuum dryer to -0.1 MPa for 20 min. Remove the container and cure it at 80 °C for 3 h. Repeat the above steps once to obtain the composite precursor.
[0062] Step 5: Place the composite precursor in a plasma-enhanced chemical vapor deposition system (RF plasma source, 13.56 MHz, 500 W), and heat it to 1000 ℃ at a rate of 5 ℃ / min under a flowing high-purity nitrogen atmosphere, hold it at that temperature for 1 h; then heat it to 1300 ℃ at a rate of 2 ℃ / min, hold it at that temperature for 3 h, cool it with the furnace, and ultrasonically disperse it to obtain the urchin-like MgO-MgSiN2 composite powder.
[0063] XRD diffraction patterns show that the urchin-like MgO-MgSiN2 composite powder prepared in this embodiment is mainly composed of MgSiN2 and MgO; SEM morphology observation shows that a small number of short rod-shaped MgSiN2 whiskers are radially grown on the surface of MgO particles, and the whiskers are relatively uniformly distributed; the BET specific surface area of the urchin-like MgO-MgSiN2 composite powder in this embodiment is 22.6 m². 2 / g.
[0064] Example 2
[0065] The preparation steps of a MgO-MgSiN2 composite powder with a sea urchin-like structure are as follows:
[0066] Step 1: Place the high-silicon magnesite powder in a tubular atmosphere furnace and calcine it at 450 ℃ for 1.5 h. Cool it in the furnace, crush it, and sieve it to obtain magnesium oxide powder with uniform particle size, good dispersibility, and pseudomorphic characteristics of mother salt.
[0067] Step 2: Under an argon atmosphere, 3.0 parts by mass of organopolysilazane, 2.25 parts by mass of diethylmagnesium in n-hexane solution (based on magnesium element mass), and 45 parts by mass of anhydrous toluene are mixed and stirred at 450 r / min for 3 h. The solvent is removed by vacuum distillation to obtain magnesium-containing polysilazane precursor.
[0068] Step 3: Dissolve all the magnesium-containing polysilazane precursor obtained in Step 2 in 30 parts by mass of anhydrous toluene, add 1.3 parts by mass of cobalt nitrate hexahydrate, and stir at 250 r / min until completely dissolved to obtain the impregnation solution.
[0069] Step 4: Place 10 parts by weight of magnesium oxide powder with the pseudomorphic characteristics of mother salt in an impregnation container, add 60 parts by weight of impregnation liquid, and vacuum in a vacuum dryer to -0.1 MPa for 25 min. Remove the container and cure it at 90 °C for 4 h. Repeat the above steps twice to obtain the composite precursor.
[0070] Step 5: Place the composite precursor in a plasma-enhanced chemical vapor deposition system (RF plasma source, 13.56 MHz, 600 W), and heat it to 1050 ℃ at a rate of 6 ℃ / min under a flowing high-purity nitrogen atmosphere, hold for 1.5 h; then heat it to 1330 ℃ at a rate of 3 ℃ / min, hold for 3.5 h, cool with the furnace, and ultrasonically disperse to obtain the sea urchin-like MgO-MgSiN2 composite powder.
[0071] XRD diffraction patterns show that the urchin-like MgO-MgSiN2 composite powder prepared in this embodiment is mainly composed of MgSiN2 and MgO. SEM morphology observation shows that the density of short rod-shaped MgSiN2 whiskers radially grown on the surface of MgO particles is increased compared to Example 1, and the whiskers are uniformly distributed radially. The BET specific surface area of the urchin-like MgO-MgSiN2 composite powder described in this embodiment is 20.3 m². 2 / g.
[0072] Example 3
[0073] The preparation steps of a MgO-MgSiN2 composite powder with a sea urchin-like structure are as follows:
[0074] Step 1: Place the high-silicon magnesite powder in a tubular atmosphere furnace and calcine it at 500 ℃ for 2 h. Cool it in the furnace, crush it, and sieve it to obtain magnesium oxide powder with uniform particle size, good dispersibility, and pseudomorphic characteristics of mother salt.
[0075] Step 2: Under the protection of argon atmosphere, 3.0 parts by mass of organopolysilazane, 3.5 parts by mass of diethylmagnesium in n-hexane solution (based on magnesium element mass), and 35 parts by mass of anhydrous toluene are mixed and stirred at 500 r / min for 4 h. The solvent is removed by vacuum distillation to obtain magnesium-containing polysilazane precursor.
[0076] Step 3: Dissolve all the magnesium-containing polysilazane precursors obtained in Step 2 in 45 parts by mass of anhydrous toluene, add 2.5 parts by mass of cobalt nitrate hexahydrate, and stir at 300 r / min until completely dissolved to obtain the impregnation solution.
[0077] Step 4: Place 10 parts by weight of magnesium oxide powder with the pseudomorphic characteristics of mother salt in an impregnation container, add 90 parts by weight of impregnation liquid, and vacuum in a vacuum dryer to -0.1 MPa for 30 min. Remove the container and cure it at 100 °C for 5 h. Repeat the above steps 3 times to obtain the composite precursor.
[0078] Step 5: Place the composite precursor in a plasma-enhanced chemical vapor deposition system (RF plasma source, 13.56 MHz, 700 W), and heat it to 1100 ℃ at a rate of 7 ℃ / min under a flowing high-purity nitrogen atmosphere, hold for 2 h; then heat it to 1360 ℃ at a rate of 4 ℃ / min, hold for 4 h, cool with the furnace, and ultrasonically disperse to obtain the sea urchin-like MgO-MgSiN2 composite powder.
[0079] XRD diffraction patterns show that the urchin-like MgO-MgSiN2 composite powder prepared in this embodiment is mainly composed of MgSiN2 and MgO. Figure 1As shown; SEM morphology observation revealed that the surface of MgO particles was covered by MgSiN2 whiskers, and the whiskers were regularly arranged and grew outward in a radial pattern. The whiskers were tightly bonded to the MgO matrix interface, as shown in the image. Figure 2 As shown; the BET specific surface area of the urchin-like MgO-MgSiN2 composite powder described in this embodiment is 15.8 m². 2 / g.
[0080] Example 4
[0081] The preparation steps of a MgO-MgSiN2 composite powder with a sea urchin-like structure are as follows:
[0082] Step 1: Place the high-silicon magnesite powder in a tubular atmosphere furnace and calcine it at 550 ℃ for 2.5 h. Cool it in the furnace, crush it, and sieve it to obtain magnesium oxide powder with uniform particle size, good dispersibility, and pseudomorphic characteristics of mother salt.
[0083] Step 2: Under an argon atmosphere, 3.0 parts by mass of organopolysilazane, 4.75 parts by mass of diethylmagnesium in n-hexane solution, and 25 parts by mass of anhydrous toluene are mixed and stirred at 550 r / min for 5 h. The solvent is removed by vacuum distillation to obtain magnesium-containing polysilazane precursor.
[0084] Step 3: Dissolve all the magnesium-containing polysilazane precursor obtained in Step 2 in 60 parts by mass of anhydrous toluene, add 3.8 parts by mass of cobalt nitrate hexahydrate, and stir at 350 r / min until completely dissolved to obtain the impregnation solution.
[0085] Step 4: Place 10 parts by weight of magnesium oxide powder with the pseudomorphic characteristics of mother salt in an impregnation container, add 120 parts by weight of impregnation liquid, and vacuum in a vacuum dryer to -0.1 MPa for 35 min. Remove the container and cure it at 110 °C for 6 h. Repeat the above steps 4 times to obtain the composite precursor.
[0086] Step 5: Place the composite precursor in a plasma-enhanced chemical vapor deposition system (RF plasma source, 13.56 MHz, 800 W), and heat it to 1150 ℃ at a rate of 8 ℃ / min under a flowing high-purity nitrogen atmosphere, hold for 2.5 h; then heat it to 1390 ℃ at a rate of 5 ℃ / min, hold for 4.5 h, cool with the furnace, and ultrasonically disperse to obtain the sea urchin-like MgO-MgSiN2 composite powder.
[0087] XRD diffraction patterns show that the urchin-like MgO-MgSiN2 composite powder prepared in this embodiment is mainly composed of MgSiN2 and MgO. SEM morphology observation shows that a large number of MgSiN2 whiskers grow on the surface of MgO particles, the whiskers are relatively uniformly distributed, and a small number of MgSiN2 particles are attached to the surface. The BET specific surface area of the urchin-like MgO-MgSiN2 composite powder described in this embodiment is 14.2 m². 2 / g.
[0088] Example 5
[0089] The preparation steps of a MgO-MgSiN2 composite powder with a sea urchin-like structure are as follows:
[0090] Step 1: Place the high-silicon magnesite powder in a tubular atmosphere furnace and calcine it at 600 ℃ for 3 h. Cool it in the furnace, crush it, and sieve it to obtain magnesium oxide powder with uniform particle size, good dispersibility, and pseudomorphic characteristics of mother salt.
[0091] Step 2: Under an argon atmosphere, 3.0 parts by mass of organopolysilazane, 6.0 parts by mass of diethylmagnesium in n-hexane solution (based on magnesium element mass), and 15 parts by mass of anhydrous toluene are mixed and stirred at 600 r / min for 6 h. The solvent is removed by vacuum distillation to obtain magnesium-containing polysilazane precursor.
[0092] Step 3: Dissolve all the magnesium-containing polysilazane precursor obtained in Step 2 in 75 parts by mass of anhydrous toluene, add 5.0 parts by mass of cobalt nitrate hexahydrate, and stir at 400 r / min until completely dissolved to obtain the impregnation solution.
[0093] Step 4: Place 10 parts by weight of magnesium oxide powder with the pseudomorphic characteristics of mother salt in an impregnation container, add 150 parts by weight of impregnation liquid, and vacuum in a vacuum dryer to -0.1 MPa for 40 min. Remove the container and cure it at 120 °C for 7 h. Repeat the above steps 5 times to obtain the composite precursor.
[0094] Step 5: Place the composite precursor in a plasma-enhanced chemical vapor deposition system (RF plasma source, 13.56 MHz, 900 W), and heat it to 1200 ℃ at a rate of 9 ℃ / min under a flowing high-purity nitrogen atmosphere, hold for 3 h; then heat it to 1420 ℃ at a rate of 6 ℃ / min, hold for 5 h, cool with the furnace, and ultrasonically disperse to obtain the sea urchin-like MgO-MgSiN2 composite powder.
[0095] XRD diffraction patterns show that the urchin-like MgO-MgSiN2 composite powder prepared in this embodiment is mainly composed of MgSiN2 and MgO; SEM morphology observation shows that MgSiN2 whiskers grow on the surface of MgO particles, and the number of MgSiN2 particles attached to the whisker surface is increased compared with Example 4; the BET specific surface area of the urchin-like MgO-MgSiN2 composite powder in this embodiment is 12.3 m² / g. 2 / g.
[0096] This specific implementation method has the following advantages compared with the prior art:
[0097] This invention utilizes atomic-level homogeneous mixing of polymer precursors to chemically graft Mg atoms onto polysilazane molecular chains. This grafting process involves the dealkylation reaction of active NH bonds on the polysilazane molecular chains with diethylmagnesium, forming chemical bonds that anchor Mg atoms in the molecular backbone in a coordinated manner. This confines the nucleation sites of MgSiN2 during pyrolysis to the molecular chain segment scale, achieving homogeneous mixing of Mg and Si at the molecular scale and resulting in a more uniform distribution of MgSiN2 in the pyrolysis products. Semi-quantitative analysis of XRD patterns reveals that the intensity ratio of MgSiN2 to MgO diffraction peaks initially increases and then decreases under different magnesium excess levels. When the magnesium excess is moderate, the MgSiN2 / MgO peak intensity ratio reaches its maximum, indicating an optimal magnesium excess range within which the amount of MgSiN2 generated is relatively high and the product phase purity is superior (wherein, the XRD pattern of the MgO-MgSiN2 composite powder prepared in Example 3 is shown in [reference needed]). Figure 1 The method of this invention can achieve in-situ generation of MgSiN2 in the MgO mother salt pseudo-matrix, and the yield of MgSiN2 can be optimized by adjusting the magnesium-silicon ratio. At the same time, it avoids incomplete reaction and impurity phase formation caused by uneven distribution of raw materials during mechanical mixing.
[0098] This invention completes the entire reaction process in powder form, eliminating the need for a sintering densification stage. This fundamentally avoids the limitations of solid-phase sintering aids in promoting particle rearrangement and interstitial densification. The original nanopores inside the pseudomorphic mother salt are not eliminated by sintering, but are filled by MgSiN2 nanoparticles generated in situ by the pyrolysis of the precursor. This transforms the pores from structural defects into a space for the composite reinforcing phase. The MgSiN2 whiskers that are radially grown on the surface form a continuous coating layer. The overall density of the urchin-like composite powder obtained by this invention is significantly improved.
[0099] This invention introduces cobalt at the precursor molecular level, avoiding the problems of easy agglomeration and deactivation of external catalysts at high temperatures, ensuring the uniform distribution and stability of cobalt active components under high temperature conditions, and further improving the amount of MgSiN2 whiskers generated on the powder surface.
[0100] The MgO-MgSiN2 composite powder prepared by this invention has a unique sea urchin-like structure, such as... Figure 2 As shown, MgO particles serve as the core, and their internal pores provide a nanoscale confined space for precursor pyrolysis. In situ, dispersed MgSiN2 nanoparticles are generated in the internal pores, strengthening the matrix through a pinning effect. The generation of MgSiN2 is not constrained by surface densification, and the internal pores are fully utilized, resulting in a more complete reaction. MgSiN2 whiskers on the framework surface radiate outward along the lattice matching direction, and a strong interface is formed between the whiskers and the MgO core through in-situ chemical bonding, avoiding the interface debonding problem in mechanical mixing.
[0101] In summary, the urchin-like MgO-MgSiN2 composite powder prepared by this invention has the characteristics of high conversion rate, high product purity, and dense structure, making it suitable for use in magnesia-based unshaped refractories (such as magnesia castables). Utilizing the physical barrier effect of its core-shell coating structure, it inhibits the contact between the internal MgO components and water vapor, thereby slowing down the hydration reaction process and reducing the risk of volume expansion and structural cracking of unshaped refractories during curing and heating drying stages. Alternatively, it can be used as a modifying additive for anti-oxidation and anti-slag erosion in carbon-containing refractory products (magnesia-carbon bricks, magnesia-carbon unfired bricks) to improve the structural stability of products under high-temperature service environments.
[0102] The above detailed embodiments describe the implementation of the present invention; however, the present invention is not limited to the specific details described in the above embodiments. Within the scope of the claims and technical concept of the present invention, various simple modifications and changes can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing a MgO-MgSiN2 composite powder with a sea urchin-like structure, characterized in that, Includes the following steps: In an inert gas atmosphere, an organic solvent solution of organopolysilazane and alkyl magnesium is mixed with a hydrocarbon inert organic solvent, stirred evenly, and then the solvent is removed to obtain a magnesium-containing polysilazane precursor. The magnesium-containing polysilazane precursor is dissolved in a hydrocarbon inert organic solvent, a soluble cobalt salt is added, and the mixture is stirred until completely dissolved to obtain an impregnation solution; wherein the mass ratio of the organopolysilazane, the organic solvent solution of alkyl magnesium, and the soluble cobalt salt is 3.0:(1.0~6.0):(0.1~5.0), and the organic solvent solution of alkyl magnesium is based on the mass of magnesium element; Magnesium oxide powder with pseudomorphic characteristics of mother salt was placed in an impregnation container, impregnation liquid was added, and after vacuum impregnation, it was subjected to heat curing treatment; the above vacuum impregnation and heat curing steps were repeated 1 to 5 times to obtain the composite precursor; The composite precursor was placed in a plasma-enhanced chemical vapor deposition system and heated to 1000-1200 °C at a rate of 5-9 °C / min under a nitrogen atmosphere, and held for 1-3 h; then heated to 1300-1420 °C at a rate of 2-6 °C / min, and held for 3-5 h to obtain a sea urchin-like MgO-MgSiN2 composite powder.
2. The method for preparing a sea urchin-like MgO-MgSiN2 composite powder according to claim 1, characterized in that, The alkyl magnesium is selected from one or more of dimethyl magnesium, diethyl magnesium, and di-n-butyl magnesium.
3. The method for preparing a sea urchin-like MgO-MgSiN2 composite powder according to claim 1, characterized in that, The soluble cobalt salt is selected from one or more of cobalt nitrate hexahydrate, cobalt chloride, cobalt acetate, and cobalt sulfate.
4. The method for preparing a sea urchin-like MgO-MgSiN2 composite powder according to claim 1, characterized in that, The magnesium oxide powder with the pseudomorphic characteristics of mother salt is obtained by calcining high-silica magnesite powder at 400~600 ℃ for 1~3 h, followed by cooling, crushing and sieving.
5. The method for preparing a sea urchin-like MgO-MgSiN2 composite powder according to claim 1, characterized in that, The mass ratio of the magnesium oxide powder with the pseudomorphic characteristics of mother salt to the impregnation liquid is 10:(30~150).
6. The method for preparing a sea urchin-like MgO-MgSiN2 composite powder according to claim 5, characterized in that, The vacuum impregnation operation is as follows: the impregnation container containing magnesium oxide powder with the pseudo-characteristics of mother salt and the impregnation liquid is placed in a vacuum dryer, a vacuum is drawn, and the process is maintained for 20 to 40 minutes.
7. The method for preparing a sea urchin-like MgO-MgSiN2 composite powder according to claim 5, characterized in that, The heat curing treatment is performed at 80~120 ℃ for 3~7 h.
8. The method for preparing a sea urchin-like MgO-MgSiN2 composite powder according to claim 1, characterized in that, The plasma source of the plasma-enhanced chemical vapor deposition system is a radio frequency plasma source with a radio frequency of 10~50 MHz and a radio frequency power of 500~900 W.
9. The method for preparing a sea urchin-like MgO-MgSiN2 composite powder according to claim 1, characterized in that, The hydrocarbon inert organic solvent is selected from one or more of n-hexane, toluene, and xylene.
10. The urchin-like MgO-MgSiN2 composite powder prepared by the preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
Magnesium oxide-silicon magnesium nitride powder based on high-silicon magnesite and preparation method of magnesium oxide-silicon magnesium nitride powder
CN115465845A
Preceramic compositions and ceramic products
US5006492A
